The causal configurations of provincial health policy innovation in China: an analysis of the food safety standard filing policy - Li, Li; Han, Guanghua; Chen, Yanting; Zhang, Zilin; Fu, Xiao (Frontiers in Public Health, 2023)
Introduction According to China’s Food Safety Law of 2015, the filing of food safety enterprise standards is a policy innovation led by p9rovincial governments in China. However, there are significant differences in the development of the “Food Safety Enterprise Standard Filing Policy” between provincial governments across the country. This study aims to explore the internal mechanisms driving autonomous innovation by provincial governments in the absence of administrative pressure from the central government, to better understand the policy innovation mechanism in the Chinese context. Methods Crispy Set Qualitative Comparative Analysis (csQCA) method is used to identify the innovation mechanism. Results This study found that provinces with good provincial economic resources and strong government capabilities are prone to policy innovation, and the influence of internal factors of provincial governments is stronger than that of external factors. Discussion When provincial economic resources and capacity are weak, endogenous factors in the province also help achieve proactive policy innovation by provincial governments. The research results reveal how provincial governments construct local policies in the absence of administrative pressure from the central government.